Copper homeostasis and cuproptosis: implications for neurodegenerative diseases - Tao, Feng; Lin, Mengxuan; Meng, Xiang; Huang, Linghui; Zhuo, Bifang; Jiang, Siyi; Deng, Shizhe; Meng, Zhihong; Shi, Jiangwei (Frontiers in Aging Neuroscience, 2025)
Copper (Cu) is a vital trace element required for sustaining life and is involved in numerous critical metabolic processes within the body. Cuproptosis, a newly recognized type of Cu-dependent cell death, is mechanistically distinct from apoptosis, autophagy, pyroptosis, and ferroptosis. It is characterized by abnormal Cu accumulation and aberrant interactions with key enzymes of the tricarboxylic acid (TCA) cycle, which lead to protein aggregation, loss of iron–sulfur cluster proteins, and proteotoxic stress, ultimately leading to cell death. Recent studies have revealed that Cu dyshomeostasis and cuproptosis are intricately linked to the pathological progression of several neurodegenerative diseases, including Alzheimer’s disease (AD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS), Huntington’s disease (HD), Wilson’s disease (WD), and Menkes disease (MD). In this review, we systematically elucidate the systemic Cu metabolism, the molecular mechanisms of cuproptosis, and its intricate interplay with different neurodegenerative disorders. We also examined the relationship between cuproptosis and other types of cell death. Finally, we discuss therapeutic strategies targeting cuproptosis and Cu dyshomeostasis to combat neurodegenerative diseases and propose potential directions for future research.